Energy efficiency of residential buildings using thermal insulation of external walls and roof based on simulation analysis - Nima Amani (Energy Storage and Saving)
The objective of this study was to investigate the impact of thermal insulation on residential buildings to optimize energy consumption in northern Iran. Specifically, it evaluated the performance of polystyrene thermal insulation in reducing thermal loads through energy simulation analysis. DesignBuilder software was used as a research tool for simulation, with regional climate conditions assigned as the starting point. Energy consumption was analyzed by selecting appropriate thermal insulation for the external walls and roofs of residential buildings to achieve high energy efficiency. A residential building in Chalous city, a region with a moderate and humid climate in northern Iran, was simulated using DesignBuilder software. The study presented the minimum thermal resistance required for external walls and provided results demonstrating the effect of optimal thermal insulation implementation on reducing building energy consumption and carbon emissions. The simulation results showed that optimal thermal insulation reduced heat loss by 54.8% in walls and 53.5% in roofs. By simultaneously selecting suitable thermal insulation for both walls and roofs in moderate and humid climates, the study achieved the greatest energy savings (summer and winter: 47.2%). This optimization not only reduces costs associated with thermal and cooling energy loss but also enhances building performance against atmospheric factors and decreases energy consumption in the building sector.